Actual long-term outcome of T1 and T2 pancreatic ductal adenocarcinoma after surgical resection. (April 2017) - Han, San Hyup; Heo, Jin Seok; Choi, Seong Ho; Choi, Dong Wook; Han, In Woong; Han, Sunjong; You, Yung Hun
Abstract: Background: The prognosis for patients with pancreatic cancer is extremely poor. The diagnosis of pancreatic ductal adenocarcinoma at an early stage is uncommon. The purpose of this study was to analyze the clinicopathological characteristics of patients with pathologically proven pancreatic ductal adenocarcinoma following surgical resection and their actual 5 year survival rates, especially for those with T1 and T2 early stage cancer. Methods: Retrospective analysis was performed for 433 patients with pancreatic ductal adenocarcinoma who underwent resection at Samsung medical center between May 1995 and December 2010. The actual 5 year survival rates and prognostic factors were analyzed. Results: Multivariate analysis showed that positive resection margin, poor differentiation, large tumor size, large amount of blood loss, and T3/T4 were independent prognostic factors on overall survival. The median survival for T1/T2 stage was 71.7 months compared to 16.1 months for those with T3/T4 stage. The actual 5 year survival rates for T1/T2 and T3/T4 stages were 66.7% and 18.4%, respectively. Conclusions: T stage is one of the strongest independent prognostic factor for overall survival of patients with pancreatic cancer. T1/T2 pancreatic ductal adenocarcinoma showed good survival outcome. Therefore, additional efforts are needed to improve the screening for early detection. Highlights: Pancreatic ductal adenocarcinoma is not often diagnosed at an early stage. Retrospective analysis was performed for pancreatic ductal adenocarcinoma. T1/T2 pancreatic ductal adenocarcinoma showed good survival outcome. Additional efforts are needed to improve the screening for early detection.